Epidemiological aspects of Lynxacarus radovskyi – Literature review (Research, Society and Development, 2022)
Dermatological diseases are increasingly gaining prominence in the routine of veterinary clinics and hospitals, and within this context, the lynxacariasis caused by the mite Lynxacarus radovskyi has presented a significant occurrence in domestic cats. Thus, the aim of this study is to make a narrative literature review about this agent, addressing the epidemiology, diagnostic methods and treatment. Finally, it is considered that the main purpose of the study was achieved, since it is an agent that is not commonly found in domestic animals; however, it is extremely important to know about its causes, epidemiology, therapeutic protocols and prophylaxis in order to control its prevalence and infection rates in its hosts.